Characterizing the induced flow through the cavity of a wall solar chimney under the effects of the opening heights. (March 2023) - Nguyen, Y Q; Nguyen, Viet T
Using solar chimneys in buildings can enhance the thermal insulation of the building envelope and provide sufficient ventilation and cooling. The performance of a solar chimney is strongly affected by its configurational factors. This work examines the effects of the opening heights on the flow field in the cavity of a wall solar chimney with a Computational Fluid Dynamics (CFD) model. Both cases of equal and unequal opening areas were considered. The results show that the induced flow rate increases with the opening height and gradually becomes constant as the opening height is about 2.0–3.0 and 5.0–6.0 times the air gap for heating the left wall (HLW) and the right wall (HRW) of the air cavity, respectively. Particularly, using equal inlet and outlet heights that are equal to the air gap reduces the flow rate of 27% for HLW and 85% for HRW compared to the maximum ones. The optimal design of a wall solar chimney to achieve maximum flow rate is proposed for two cases of heating, that is, (a) for HLW, equal opening heights which are twice the air gap, and (b) for RHW, the inlet height equal to the air gap, and the outlet height equal to five times the air gap.